Penerapan Metode Multistrategi Sebagai Upaya dalam Meningkatkan Aktivitas dan Hasil Belajar Siswa terhadap Pembelajaran Teks Proposal - Herniyastuti, Herniyastuti; Liska, Liska; Yusuf M, A.Yusdarwati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to increase the activity and results of learning Indonesian during the Covid-19 pandemic through a multi-strategic method in class XI MIPA 2 students of SMA Negeri 2 Soppeng. The research conducted was a classroom action research regarding the application of multi-strategic methods that aimed to increase student learning activities and outcomes in learning proposal texts at SMA Negeri 2 Soppeng, Soppeng Regency. This study used 2 cycles, namely cycle I and cycle II which consisted of planning, implementing, observing, and reflecting. Data collection techniques used test and non-test techniques. Data analysis techniques using quantitative and qualitative analysis techniques. Based on the results of data analysis, this research was considered sufficient and successful, because the students' learning outcomes had reached 75% of the KKM and mastery in class had reached â‰¥75%. In conclusion, the multi-strategy method can improve the quality of learning. This increase was caused by an increase in student learning activity which was created by good interaction and collaboration between teachers and students, as well as students and students in a democratic manner so that the learning process was very dynamic. Keywords: Student Activity, Learning Outcomes, Multistrategic Method